Modern Methods of Surgical Treatment of Heart Diseases on the Example of Cardiac Surgery for Chd - Vasilevich, Paskhin Igor; Borzkhadzhievich, Gazaliev Abdul-Bakiei; Dmitrievna, Alekseeva Tatiana; Kamilovich, Kaibov Akim (International Journal of Psychosocial Rehabilitation, 2020)
Abstract–cardiac surgery is understood as the treatment of acquired or congenital heart defects by surgery. This article considers cardiac surgery as the only option of this method of treatment of coronary heart disease (CHD) and its complications in severe cases. To date, there are three types of treatment for CHD by surgical intervention: endovascular method, aorto-coronary bypass surgery and coronary stenting. The operation is aimed at improving blood flow in the ischemic heart. Additionally this operation can eliminate complications of IHD, such as an aneurysm, acute mitral valve insufficiency, the results of the infarction and infarct defects of the interventricular septum. From the above the most popular method is the aorto-coronary method bypass surgery, consisting of a bribe from the legs of a large subcutaneous area veins – it is from it that the shunt will be formed in the future. In most cases, coronary heart disease can be cured only by surgical method because in this case drug therapy is not available it is always effective. This article describes the time spent in the department of cardiac surgery research on heart surgery for CHD coronary bypass surgery: the main stages of the operation, advantages of the method, observations and results in postoperative period.